Trading off between control and autonomy: a narrative review around de-design. Issue 1 (2nd January 2020) - Cabitza, Federico; Locoro, Angela; Ravarini, Aurelio
ABSTRACT: In this work, we provide an overview of contemporary perspectives of design that may challenge the traditional design of IT and socio-technical systems. Our starting metaphor is that of 'wicked problems', where the singularity, incompleteness and intrinsic uncertainty of real world settings foregrounds how the worldview that designers offer to practitioners may be optimal in theory but useless in practice. To go beyond traditional notions of design and designer, we intercepted insights coming from minoritarian voices in both theoretic and practice-based design fields. 'De-design' is a term we coined to encompass this wide spectrum of approaches that make more resilient and sustainable information artifact, de-emphasize design as a theoretical construct, and reconsider practice as the leading principle of digital innovation. This paper is a narrative review of voices in an extensive array of fields: from Information Systems to Human-Computer Interaction, from End-User Development to Critical Design, from Software Design to Design Studies. Our contribution retraces the motivational roots of de-design and tries to characterise de-design by filling relational gaps between disparate approaches and by bringing them back to IT and socio-technical design, to make digital artifacts sustainable in all of the new environmental, organisational and cultural spaces near to come.